The feedback effects of canopy architecture : why are African acacias flat-topped? - McLean, Phil (Department of Biological Sciences, 2017)
Only the African acacias have a so-called flat topped crown. This study identifies this architecture using the simple measures of height, diameter and spread. In this way the flat-topped species are identified and differentiated from the other acacia species (A. nilotica & A. tortilis). It has been suggested that this shape is an anti-herbivore mechanism. We demonstrate how these trees spend a lot of energy in defence, which indicates that the canopy shape is a poor anti-herbivore device. Measurements of the height of grass outside the canopies indicate that these species inhabit areas of long grass. At the same time, our data show that at least one of these species (A. nilotica) is extremely fire sensitive (60% mortality). The effect which saves these trees from fire is shorter grass beneath their crowns providing a low-fuel fire buffer for the trunk. However, none of the conventional effects of canopy are able to cause this effect (shade, nutrients). We propose that the shade and nutrient-rich undercanopy grass (as well as the pods of these animal-dispersed trees) encourages large grazing mammals to spend time under these trees. These animals then, are responsible for lowering the height of the grass cover by grazing and trampling, and hence save the trees from fire. We suggest an animal - flat-topped tree mutualism where food and shade are exchanged for seed dispersal and fire protection.